PENGARUH IDEALISME, RELATIVISME, DAN LOVE OF MONEY PADA PERSEPSI MAHASISWA AKUNTANSI TENTANG KRISIS ETIKA AKUNTAN - Sugiantari, Ni Kadek; Widanaputra, A.A.G.P (E-Jurnal Akuntansi; Vol 17 No 3 (2016), 2016)
This study aims to determine students' perceptions of accounting related to the ethical crisis that occurred within the scope of accounting, especially in cases of code violations involving accountants. Furthermore, this study examines the effect of idealism, relativism, and the love of money against their assessment of the ethical crisis accountant. This research was conducted at the Faculty of Economics and Business, University of Udayana. This research method is probability sampling. Data collected through questionnaires. The sample was 188 students S1 Accounting Faculty of Economics and Business, University of Udayana who are already taking courses Auditing 1. The data analysis technique used is multiple linear regression were processed using SPSS 22. Results of hypothesis testing showed that the Idealism and Love of money give a negative effect on accounting student opinion on the ethical crisis accountant. Whereas relativism positive effect on students' perceptions of ethical crisis accountant.
Keywords: Idealism, Relativism, Love of Money, Accounting Scandal, Perception